Data on cytochrome c oxidase assembly in mice and human fibroblasts or tissues induced by SURF1 defect - Kovářová, Nikola; Pecina, Petr; Nůsková, Hana; Vrbacký, Marek; Zeviani, Massimo; Mráček, Tomáš; Viscomi, Carlo; Houštěk, Josef (Data in brief, 2016)
This paper describes data related to a research article entitled "Tissue- and species-specific differences in cytochrome c oxidase assembly induced by SURF1 defects" [1]. This paper includes data of the quantitative analysis of individual forms of respiratory chain complexes I, III and IV present in SURF1 knockout (SURF1 (-/-) ) and control (SURF1 (+/+) ) mouse fibroblasts and tissues and in fibroblasts of human control and patients with SURF1 gene mutation. Also it includes data demonstrating response of complex IV, cytochrome c oxidase (COX), to reversible inhibition of mitochondrial translation in SURF1 (-/-) mouse and SURF1 patient fibroblast cell lines.
Keywords: Cytochrome c oxidase; COX, Cytochrome c oxidase; Respiratory chain; DOX, doxycycline; SURF1; Knockout; Doxycycline